The poetics of difference and displacement : twentieth-century Chinese-Western intercultural theatre - Tian, Min, 1958- (Hong Kong University Press, 2008)
"The Poetics of Difference and Displacement is the first book in English that systematically investigates the twentieth-century Chinese-Western intercultural theatre. It demonstrates that what is central to the making of the twentieth-century Chinese-Western intercultural theatre is what the author calls the poetics of difference and displacement, which underlies its most significant aspects." "The Poetics of Difference and Displacement views intercultural theatre as a process of displacement and re-placement of culturally specified and differentiated theatrical forces, rejecting any universalist or essentialist presumptions. It approaches the twentieth-century Chinese-Western intercultural theatre from an aesthetic as well as a social-historic, cultural-political perspective. It examines both the Western theatre's interpretation and interculturation of the Chinese theatre by Bertolt Brecht, Vsevolod Meyerhold, Gordon Craig, Eugenio Barba and Peter Sellars and modern Chinese theatre's interpretation and interculturation of the Western theatre." "This book will appeal to a broad range of readers including academics and students in theatre, performance, and cultural studies. It will also be of interest to a general audience of Chinese culture and intercultural communication."--Jacket.